A STUDY OF PSYCHIATRIC COMORBIDITY IN ALCOHOL DEPENDENCE - Vohra, A. K. (Medknow Publications, 2003)
The diagnosis of comorbid psychiatric conditions have important clinical ramifications as the outcome is poorer with multiple disorders. Various studies have shown that alcohol abuse has severe adverse effects on the course of metal illness and vice versa. Only a little data on the subject are available from our country. We interviewed 30 patients suffering from alcohol dependence using SCID - I & SCID - II. Seventy six percent of the sample had axis - I comorbid diagnosis and 40% had an axis -II diagnoses. Depressive disorder and cluster B personality disorders were the most common comorbid diagnosis.